Penerapan Media Pembelajaran Pada Mata Pelajaran Sistem Elektropnuematik Berbasis website - Hajiji Hajiji; Ilham Akbar Darmawan; Mohammad Fatkhurrokhman (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
This study aims to determine the level of feasibility of the website of the subject electropneumatic controlsystem. Based on early observation data, the Department of Industrial Automation Engineering does not yethave a learning website to support the electropneumatic system learning process. Thus, this study used a research and development (R and D) model with the Waterfall method. However, the subjects involved inthis study were class XI Industrial Automation Engineering Department. The data collection techniqueschosen were interviews and questionnaires with the media evaluation sheet instrument, material evaluationsheet, and user assessment sheet which presented on a Likert scale. The results showed that the websitesupported the learning of electropneumatic system subject had been tested in 8 meetings in the class XI ofIndustrial Automation Engineering. The results of this development research showed that the mediafeasibility test got an average of 75% in the "appropriate" category, the results of the material evaluation testreached an average of 49.7% in the "adequate" category and the assessments from teacher and studenttook an average of 55% with "decent" category. It can be concluded that the website developed iscategorized as "appropriate" to be applied as a learning support in the Department of Industrial AutomationEngineering, especially in the subject of electropneumatic systems. Based on the results, it can besuggested website development on other subject matter to support the success of the learning process.